Analisis Hidrogeokimia Dan Logam Berat Pada Air Tanah Menggunakan Metode WQI dan HPI Untuk Keperluan Higiene Sanitasi Kabupaten Belitung Timur - Putri, Maya Aiko Salsabila; Putranto, Thomas Triadi; Santi, Narulita (TEKNIK, 2023)
Kelapa Kampit is one of the tin-producing districts in East Belitung, which is composed of the Kelapa Kampit Formation. This mining activity affects water quality, which, of course, is also influenced by geological formations. This study aims to analyze the hydrogeochemistry and heavy metals in shallow groundwater in Kelapa Kampit District using water quality indexes in the form of water quality index and heavy metal pollution index methods. Hydrogeochemical test results showed a pH value of water 4 – 6.77 in the acidic category, a DHL value of 20 – 145 μS/cm, and a TDS value of 14 – 111 mg/L. From the visualization of chemical data, groundwater has various facies. The results of the Stiff Diagram show that water contains predominant calcium, magnesium, sulfate, and bicarbonate ions. The Gibbs diagram results show that the water has not been contaminated. The results of heavy metal testing also showed that the values of Fe2+, Mn2+, Pb2+, Zn2+, and Cu2+ were classified as low, and Al3+ was quite high. The results of water quality testing using the water quality index showed that the research area had excellent water quality, and the results of the heavy metal testing using the HPI method showed a low heavy metal contamination value. Based on hydrogeochemical and heavy metal analysis of shallow groundwater, Kelapa Kampit District has good groundwater quality for sanitation hygiene purposes.